Pulmonary Health of Traffic Policemen in Low Air-Polluted Bogor Area - Harris Abdullah; Jamal Zaini; Budhi Antariksa; Agus Dwi Susanto; Faisal Yunus (Jurnal Respirologi Indonesia, 2021)
Background: Traffic policemen are very susceptible to respiratory problems due to the potential for exposure to air pollution. Therefore, this study aimed to assess respiratory health aspects of traffic policemen in Bogor, West Java. Method: Registered traffic policemen in Bogor were evaluated for respiratory symptoms, smoking habits, Fagerström Test for Nicotine Dependence (FTND) Questionnaire, chest x-ray, and spirometry. Air quality measurements were also carried out as a reference. Result: During the study period, the air quality in Bogor was classified as “Good” and below the ambient air pollutant standard. A total of 95 traffic policemen participated with a mean age of 37.3±8.7 years (range 23–57 years), mean Body Mass Index (BMI) of 28.1±4.2 kg/m2, and a length of service of 3-38 years (mean of 12.3 years). Mild pulmonary function impairment was found in 7.4% of subjects. About 61% of subjects had a smoking habit but with a low addiction index (FTND) and exCO. Decreased lung function was correlated to BMI and age (P<0.05). Conclusion: Pulmonary function impairment in traffic policemen in Bogor City was correlated to age and BMI.